Improving Representational Competence with Concrete Models. Issue 2 (2nd February 2016) - STIEFF, MIKE; SCOPELITIS, STEPHANIE; LIRA, MATTHEW E.; DESUTTER, DANE
ABSTRACT: Representational competence is a primary contributor to student learning in science, technology, engineering, and math (STEM) disciplines and an optimal target for instruction at all educational levels. We describe the design and implementation of a learning activity that uses concrete models to improve students' representational competence and achievement in an undergraduate chemistry course. In the study, we embedded modeling workshops into the normal course of instruction and measured their effectiveness for improving representational competence. The results indicate that, independent of instructor, the learning activity significantly improved students' ability to identify spatial information in disciplinary diagrams and translate among molecular representations compared to students who did not complete the activity. We also compared the effectiveness of the modeling workshops to improve achievement on summative course assessments. Despite demonstrated improvement in representational competence, students who received the intervention did not perform significantly better than a control group on course assessments. Finally, we surveyed students who completed the workshops to investigate their beliefs about the utility of concrete models for learning chemistry. Students reported that concrete models are useful for a limited range of tasks. We argue that concrete models offer specific advantages to the student that may help improve representational competence, although such improvement may not generalize.